ABRASIVE EROSION STUDY on S45C CARBON STEEL USING SAND BLASTING TECHNIQUE - Naz, M.Y. (World Scientific Publishing Co. Pte Ltd, 2016)
Hydrocarbon fluids recovered from the reservoir are inevitably polluted with sand particles. Sanding is a source of several flow assurance problems in oil and gas industry. This study was aimed at investigating the effect of sand size and impact angle on the mild steel erosion by using a laboratory built sand blasting technique. S45C mild steel coupons were eroded with 45 μm and 150μm sand particles for fixed exposure time of 1 h. Although in-depth analysis revealed an increase in surface erosion with the particle size, the fine sand also notably damaged the metal surface. Topographic scanning electron microscopy (SEM) and universal scanning electron microscopy (USPM) micrographs of the steel coupons showed significantly large difference between the peak and bottom of the eroded samples as compared to the blank coupon. The erosion rates calculated for 45 and 150 μm sand particles were found in the range of 6.47mm/year to 6.84 mm/year and 8.31 mm/year to 8.79 mm/year, respectively. Additionally, a good agreement was seen among the erosion rates calculated using USPM and weight loss methods. The erosion rates calculated for coarse sand at 45° and 90° were found in the range of 4.58 mm/year to 4.72 mm/year and 8.31 mm/year to 8.79 mm/year, respectively. A large difference between the angle dependent erosion rates revealed a strong influence of the impact angle on erosion of the flow-lines. © 2016 World Scientific Publishing Company.